KAJIAN PEMBATALAN AKTA JUAL BELI TANAH YANG DISERTAI AKTA PENGAKUAN HUTANG DENGAN JAMINAN TANAH OBYEK PERJANJIAN (Studi Kasus Perkara Putusan Pengadilan Negeri Denpasar Nomor 309/Pdt.G/2006/PN.Dps) - , KOMANG PRAYOGA KUSUMA DIHARTA, Dr. Sutanto, S.H., M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is juridical normative-empirical study. Normative for this research studied law document which was court verdict also other documents investigation, whereas empirical for this research also seen and portrayed phenomena occurred within society thus field research needed. As for research juridical aspect was because examining issue studied based on law regulations or doctrines. Data used in the research was secondary data obtained through literature study and primary data obtained from field study by interview technique. From research result revealed that realty trading according to National Realty Law based on customary law, ownership rights transition happened when Trading Certificate is signed, therefore in realty trading with gradual payment, Trading Certificate will only be signed after the realty is paid off. By that means, a trading bond agreement is made during payment period hence guarantee realty trading success when the price is paid off. Realty trading accompanied by Debt Admission Certificate could be occurred because in time of Trading Certificate signing, prearranged realty price is not fully paid off thus rest of the realty price payment presented into debt admission certificate using warranty. Judge verdict in case Number 309/Pdt.G/2006/PN.Dps which cancelled realty trading accompanied by Debt Admission Certificate was improper. This was because realty trading and Debt Admission Certificate are two different law acts where realty trading was completely carried out and legally accomplished, whereas Buyer who could not settle rest of the realty price basically default to Debt Admission Certificate hence warranty within the Debt Admission Certificate is the one should be executed.